Risk factors and prevalence of burnout syndrome in the nursing profession. Issue 1 (January 2015) - Cañadas-De la Fuente, Guillermo A.; Vargas, Cristina; San Luis, Concepción; García, Inmaculada; Cañadas, Gustavo R.; De la Fuente, Emilia I.
Abstract Background The burnout syndrome is beginning to be regarded as an occupational illness of high prevalence among nursing in Spain. Individuals suffering from the syndrome manifest important health problems. More information about prevalence and risk factors for burnout is needed to prevent the syndrome and to determine the most appropriate clinical interventions when the disorder appears. Objectives Burnout levels were evaluated in a group of nurses. The objectives of this study were to estimate the prevalence of burnout, to identify the variables related to burnout and to propose a risk profile for this syndrome among the nursing personnel. Setting The study was carried out in public health centers in Andalusia (Spain). Methods The sample consisted of 676 nursing professionals from public health centers. Dependent variables were the three Burnout dimensions: emotional exhaustion, depersonalization and personal accomplishment. Independent variables were socio-demographic, organizational, personality-related variables. Results The nurses manifested average to high burnout levels. There were statistically significant differences in burnout levels associated with the following variables: age, gender, marital status, having children, level of healthcare, type of work shift, healthcare service areas and conducting administrative tasks. Burnout was also associated with personality-related variables. Conclusions The prevalence of burnout among nursing professionals is high. Gender, age, marital status, level of healthcare, work shift and healthcare service areas predicted at least one of the dimensions of the syndrome. Neuroticism, agreeability, extraversion and conscientiousness are personality traits that predict at least two of the dimensions of burnout syndrome in nurses. Therefore, personality factors should be considered in any theory of risk profiles for developing burnout syndrome in the nursing profession.